Kepastian Hukum bagi Pemegang Polis dalam Kasus Gagal Bayar Perusahaan Asuransi: Analisis Normatif - Harlian Satria Wilwatikta; Malik Madya Jaya Pratama; Falah Ramadhani; Cindi Fadila; Garnis Putri Shima (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The phenomenon of insurance company defaults indicates the existence of legal uncertainty that directly impacts the weak protection afforded to policyholders as the aggrieved party in the contractual relationship. This situation reflects a gap between applicable legal norms and their implementation in practice, particularly regarding supervision, transparency, and dispute resolution mechanisms in the financial services sector. This study aims to analyze legal certainty for policyholders in cases of insurance company defaults through a normative legal approach. The methods used include legislative and conceptual approaches, utilizing primary, secondary, and tertiary legal sources analyzed qualitatively. The research results indicate that although the regulatory framework has established protections for policyholders, its effectiveness remains limited due to weak supervision, an imbalance in the positions of the parties involved, and the suboptimal roles of the policy guarantee institution and dispute resolution mechanisms. The discussion underscores the importance of strengthening a legal protection system that is both preventive and repressive to ensure legal certainty and enhance public confidence in the insurance industry.